Multimodality in Preventive Health Posters: A Look at the Structure of the Linguistic Fact and the Ways of Transmitting the Message - González Chacón, Marcela (2022)
This research is based on the analysis of 156 Costa Rican public health preventive posters published between 2014 and 2018, considering their characteristics, classification and hierarchy of the existing resources. The aim is to delve into the description of the genre of health campaigns. The selected posters are part of digital files of the three healthcare institutions in charge: Ministry of Health, Costa Rican Social Security Administration and Institute of Alcoholism and Drug Dependency. The study was conducted using the MAXQDA 2020 qualitative analysis software, divided into three stages: corpus collection, analysis and systematization of results. The methodology was based on the multimodality approach of Kress and van Leeuwen (2006) and the linguistic act organization approach of Charaudeau (2004, 2006). It is concluded that Charaudeau's suggestion allows classifying the posters according to the most prolific production instance and the most relevant target audience; aiming, in most cases, to encourage the audience to perform an action or behavioral change, and based on relevant topics for the current Costa Rican health field. This study also reveals the presence of different modes in the texts and which ones appear in a repetitive way, indicating which are the prevailing modes used to express meaning. The results show that the verbal mode continues to play a dominant role in texts, despite the fact that they all have a multimodal character.